Constructing global order : agency and change in world politics - Acharya, Amitav (Cambridge : Cambridge University Press, 2018)
For a long time, international relations scholars have adopted a narrow view of what is global order, who are its makers and managers, and what means they employ to realize their goals. Amitav Acharya argues that the nature and scope of agency in the global order - who creates it and how - needs to be redefined and broadened. Order is built not by material power alone, but also by ideas and norms. While the West designed the post-war order, the non-Western countries were not passive. They contested and redefined Western ideas and norms, and contributed new ones of their own making. This book examines such acts of agency, especially the redefinitions of sovereignty and security, shaping contemporary world politics. With the decline of Western dominance, ideas and agency from the Rest may make it possible to imagine and build a truly global order.
Machine generated contents note: 1. Introduction: rethinking agency and change in global order; 2. Theorizing normative change; 3. Provincializing Westphalia; 4. Transforming Westphalia; 5. Redefining security; 6. Regionalism and the making of global order; 7. Conclusion and extensions.
Title from publisher's bibliographic system (viewed on 04 Apr 2018).
Off-Campus Access: Athens ID and Password Required
On-Campus Access: No User ID or Password Required
GenEd
Mode of access: Internet
Cambridge University Press
Keywords: Agent (Philosophy); East and West; International organization; Nonwestern countries